PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA - Solahudin Ayatullah Khumaeni; Aji Tuhagana; Dexi Triadinda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to examine the influence of brand image and product quality on purchasing decisions for Honda motorcycles among Management students of the 2020 Class of Buana Perjuangan University, Karawang, both partially and simultaneously. The study was conducted using descriptive and verification methods with a sample size of 107 respondents using saturated sampling techniques. The data analysis techniques used were multiple linear regression analysis, hypothesis testing, and the coefficient of determination was analyzed using the SPSS program version 25. The results of this study indicate that brand image has a significant effect on purchasing decisions and product quality has a significant effect on purchasing decisions. There is a simultan influence of brand image and product quality on purchasing decisions.